Optimizing purchasing procedures for procurement at serenity spa and salon of Hotel LMB - Sudarmini, Ni Made; Kencanawati, Anak Agung Ayu Mirah; Sukmawati, Ni Made Rai; Mazher, Muhammad Ahmad; Ariningsih, Ni Putu (Journal of Commerce, Management, and Tourism Studies, 2024)
This study investigates the purchasing procedures for the procurement of goods required by Serenity Spa and Salon at Hotel LMB. The research aims to identify inefficiencies and suggest improvements for a more streamlined process. Data was collected through a combination of qualitative interviews, observation, and document study with key personnel and quantitative analysis of procurement records over the past year. The findings highlight several areas where current practices fall short, particularly in supplier selection and inventory management. Recommendations include adopting a more rigorous supplier evaluation framework and implementing an automated inventory tracking system. These changes are expected to enhance operational efficiency, reduce costs, and ensure timely availability of high-quality products. The study concludes with a discussion of the potential impact on overall service quality at Serenity Spa and Salon.